2020
DOI: 10.20945/2359-3997000000309
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring type 1 diabetes patients during the COVID-19 pandemic in Brazil: was it useful?

Abstract: Objectives: To evaluate the performance of telemonitoring in detecting clinical and psychological needs and adherence to the protective measures imposed by the COVID-19 pandemic in addition to providing remote assistance for patients with type 1 diabetes (T1D) in a public university center in Brazil. Subjects and methods: Telemonitoring protocol included phone calls and e-mails. Patients were asked to rate COVID-19-like symptoms, psychological symptoms, epidemiological issues, and adherence to diabetes managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
15
0
3
Order By: Relevance
“…In order to maintain basic care, telemonitoring was implemented in many countries [6][7][8]. Telematic interactions were also used to help patients in developing coping strategies for managing home confinement [9][10][11] and maintaining physical activity [12,13]. Physical activity is crucial in diabetes mellitus management, especially during a pandemic, as it enhances immune response to viral infections [14]; therefore, many efforts have been performed to help patients in finding strategies to maintain it during lockdown [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain basic care, telemonitoring was implemented in many countries [6][7][8]. Telematic interactions were also used to help patients in developing coping strategies for managing home confinement [9][10][11] and maintaining physical activity [12,13]. Physical activity is crucial in diabetes mellitus management, especially during a pandemic, as it enhances immune response to viral infections [14]; therefore, many efforts have been performed to help patients in finding strategies to maintain it during lockdown [15].…”
Section: Introductionmentioning
confidence: 99%
“…This may involve providing care out of the traditional settings by using virtual health resources to disseminate information and maximize health care services for the population by means of community health agents [ 32 ]. Studies show that the follow-up of people with diabetes by using telemedicine is favourable as it enables the detection of clinical and psychological needs and provides support to the patients, including significant improvement in glycaemic levels [ 33 , 34 ]. In our sample, 31.7% participants receive care through telemedicine, and of these, 39.6% were individuals with DM1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more than half of the selected studies reveal that remote monitoring, with the help of integrated web platforms, is an important tool to ensure the glycemic range at an adequate level among children, adolescents and young adults with 1DM (15,(17)(18)(21)(22)(25)(26)(29)(30)(31)(33)(34) . Accordingly, a prospective observational study showed that structured virtual visits adequately maintain preexisting glycemic management or improve time in the target range among individuals with 1DM during an emergency, when one-to-one consultations are not allowed (35) .…”
Section: Discussionmentioning
confidence: 99%